Frontispiece: Luminescent Radical‐Excimer: Excited‐State Dynamics of Luminescent Radicals in Doped Host Crystals. Issue 9 (18th February 2019) - Kato, Ken; Kimura, Shun; Kusamoto, Tetsuro; Nishihara, Hiroshi; Teki, Yoshio
Abstract : Excimers . The excited‐state dynamics of a photostable luminescent organic radical was reported by Y. Teki and co‐workers in their Communication on page 2606 ff. The initial process in excimer formation was clarified for the first time from the viewpoint of the spin‐dynamics.